Character Education through Local Cultural Programs: Assessing the Impact of the "Tujuh Poé Atikan" Program - Mukti, Saepul; Rafsanjani, Mohammad Fikri; Fasya, Nizar Muhammad; Erihadiana, Mohamad (Jurnal Ilmiah Iqra', 2025)
Character education has become a key focus in the development of Indonesia's education system, particularly in addressing the challenges of globalization and shifting societal values. This study focuses on analyzing the impact of implementing the "Tujuh Poé Atikan" program on the development of student character. The research employs a qualitative approach, utilizing a case study method. Data collection was carried out through observation, in-depth interviews, and document analysis. The results show that the "Tujuh Poé Atikan" program makes a significant contribution to the formation of student character, encompassing nationalism, global awareness, tolerance, creativity, religiosity, respect, and independence. This study concludes that the "Tujuh Poé Atikan" program is a practical, holistic approach to character development, integrating local, national, and global values into the educational process. These findings provide recommendations for the development of character education policies in other regions as part of the effort to create intellectually and morally excellent generations.